Morphofunctional Characteristics of Freshly Isolated and Cryopreserved Human Ovarian Granulosa and Cumulus Cells - Petrushko, Marina P.; Pinyaev, Vladimir I.; Revenko, Elena B.; Volkova, Natalia A.; Chub, Natalia N. (Problems of Cryobiology and Cryomedicine, 2014)
Utilization of granulosa and cumulus cell (GCC) complex could be prospective for co-culture of gametes and embryos as a part of assisted reproductive technologies (ART), that makes important their cryopreservation. The study was performed in GCCs of women aged 25–39, who underwent the treatment of infertility by IVF. Cryopreservation of GCC suspension was carried out using 1.5 M 1,2-propane diol solution. The samples were cooled with rate of 0.3 deg/min from 25 down to –6°C, thereafter the ice crystal initiation was done, from –6 down to –35°C the cooling rate was 1 deg/min, after that the samples were plunged into liquid nitrogen and stored then at –196°C. Following thawing the GCCs retained their main features: ability for adhesion and proliferation, and hormone production. During culture of GCCs its development was delayed for 1–2 days if compared with freshly isolated cells. In 7 days after explanting the cultures of frozen-thawed GCCs appeared nearly the same as primary cultures of corresponding terms of in vitro culture. The post thaw level of hormone production by GCCs was changed: decreased by 89.9% in case of estradiol, and increased by 81.4% for progesterone if compared with the indices of freshly isolated suspensions. The obtained results testify to a possibility to isolate the GCCs and then to store in low-temperature banks for prospective use in ART. Probl Cryobiol Cryomed 2014; 24(1):57–66.